Pemberdayaan Kelompok Pembudidaya Dalam Pengaplikasian Sistem Monitoring Kualitas Air Kolam Berbasis Iot Untuk Meningkatkan Hasil Panen Ikan Mujair Desa Kaweruan, Kabupaten Minahasa Utara - Ryan Laksmana Singgeta; Ignatia R. Honandar; Pinrolinvic D. K. Manembu (Jurnal TUNAS, 2023)
In the journey to develop this business, there were two main problems that were experienced and became urgent, including: There was a time when there were tilapia fish that died in large enough numbers so that they experienced crop failure. The second problem is that cultivation groups have not been able to maintain tilapia fish seeds properly. The third problem is that cultivation groups have not been able to carry out good financial management, so they have not received the targeted profits. For this reason, the team designed a pool water quality monitoring system based on the Internet of Things (IoT) which is related to research that has been carried out and published previously. The aim of the activities carried out is to empower tilapia fish cultivation groups to be able to increase harvest yields to a good grade and more than before. In the progress stage, the team has conducted 1) training and assistance on how to properly care for tilapia fish seeds; 2) training and assistance in financial management of cultivation groups and will be continued 3) introduction of an IoT-based pond water quality monitoring system and its operation. Based on the results of the activity, it can be concluded that the tilapia fish cultivation group in Kaweruan village can understand and explain the influence of water quality on the growth of tilapia fish and is skilled in practicing how to compile a cash book using a simple application. Meanwhile, the water quality monitoring tool that has been designed can operate well and can be monitored remotely for PH, TDS, temperature, and water level values with an Internet connection.